Sequential Chemistry Toward Core–Shell Structured Metal Sulfides as Stable and Highly Efficient Visible‐Light Photocatalysts. Issue 8 (9th January 2020) - Zhang, Xingmiao; Liang, Haichen; Li, Haoze; Xia, Yuan; Zhu, Xiaohang; Peng, Liang; Zhang, Wei; Liu, Liangliang; Zhao, Tiancong; Wang, Changyao; Zhao, Zaiwang; Hung, Chin‐Te; et al.
Abstract: A universal sequential synthesis strategy in aqueous solution is presented for highly uniform core–shell structured photocatalysts, which consist of a metal sulfide light absorber core and a metal sulfide co‐catalyst shell. We show that the sequential chemistry can drive the formation of unique core–shell structures controlled by the constant of solubility product of metal sulfides. A variety of metal sulfide core–shell structures have been demonstrated, including CdS@CoSx, CdS@MnSx, CdS@NiSx, CdS@ZnSx, CuS@CdS, and more complexed CdS@ZnSx @CoSx . The obtained strawberry‐like CdS@CoSx core–shell structures exhibit a high photocatalytic H2 production activity of 3.92 mmol h −1 and an impressive apparent quantum efficiency of 67.3 % at 420 nm, which is much better than that of pure CdS nanoballs (0.28 mmol h −1 ), CdS/CoSx composites (0.57 mmol h −1 ), and 5 %wt Pt‐loaded CdS photocatalysts (1.84 mmol h −1 ). Abstract : Full CoS x jacket : Uniform metal sulfide core–shell structures with tunable chemical compositions, a clean surface and substantial lattice mismatches between them was synthesized via a universal sequential synthesis approach.